Adolescent cognitive function and risk of gestational diabetes mellitus: A retrospective population-based cohort study - Tomer Talmy; Tali Cukierman-Yaffe; Shali Mazaki-Tovi; Estela Derazne; Dorit Tzur; Arnon Afek; Avi Shina; Gabriel Chodick; Gilad Twig; Rakefet Yoeli-Ullman (PLoS ONE, 2026)
Background Gestational diabetes mellitus (GDM) is increasingly prevalent and linked with adverse maternal and neonatal outcomes. Low cognitive function in youth has been associated with various adverse metabolic outcomes. This study examined the association between adolescent cognitive function and GDM in the first pregnancy. Methods In this retrospective nationwide population-based cohort study, data from the Israel Defense Forces conscription database, including cognitive assessments conducted at approximately age 17 years (1976–2016), were linked with electronic medical records from Maccabi Healthcare Services, documenting prenatal care and gestational diabetes screening data. General intelligence test (GIT) scores were standardized into sex-specific Z-scores and categorized as low, intermediate, or high. GDM during first pregnancy was defined according to the two-step approach. Logistic regression analyses were used to calculate odds ratios (OR) for GDM. Results Among 189,663 women, 21,979 (11.6%) had low, 130,215 (68.7%) had intermediate, and 37,469 (19.8%) high GIT Z-scores; 10,187 (5.4%) developed GDM. Relative to high scores, low and intermediate scores were associated with higher odds of GDM: OR 1.17 (95% CI 1.08–1.26) and OR 1.09 (1.03–1.15), respectively. Conclusions Lower adolescent cognitive function was modestly associated with increased risk of GDM in the first pregnancy, independent of sociodemographic factors and adolescent BMI. Cognitive function may serve as an early marker of maternal metabolic health.